Occupational exposure to Bisphenol A (BPA): a reality that still needs to be unveiled - Ribeiro, Edna (2017)
Bisphenol A (BPA), 2,2-bis(4-hydroxyphenyl) propane, is one of the most utilized industrial chemicals worldwide, with the ability to interfere with/or mimic estrogenic hormones with associated biological responses. Environmental human exposure to this endocrine disruptor, mostly through oral intake, is considered a generalized phenomenon, particularly in developed countries. However, in the context of occupational exposure, non-dietary exposure sources (e.g., air and contact) cannot be underestimated. Here, we performed a review of the literature on BPA occupational exposure and associated health effects. Relevantly, the authors only identified 19 studies from 2009 to 2017 that demonstrate that occupationally exposed individuals have significantly higher detected BPA levels than environmentally exposed populations and that the detection rate of serum BPA increases in relation to the time of exposure. However, only 12 studies performed in China have correlated potential health effects with detected BPA levels, and shown that BPA-exposed male workers are at greater risk of male sexual dysfunction across all domains of sexual function; also, endocrine disruption, alterations to epigenetic marks (DNA methylation) and epidemiological evidence have shown significant effects on the offspring of parents exposed to BPA during pregnancy. This overview raises awareness of the dramatic and consistent increase in the production and exposure of BPA and creates urgency to assess the actual exposure of workers to this xenoestrogen and to evaluate potential associated adverse health effects.